Washback of an English achievement test on teachers’ perceptions at a Vietnamese university - Thu, Dinh Minh (H. : ĐHQGHN, 2020)
Research on washback, i.e. test impacts on teaching and learning in class, of high-stake English tests is prevalent. Little attention has, however, been paid to washback of an English achievement test (EAT) albeit its highly practical significance including reporting and improving teacher effectiveness right in a programme in a specific context (El-Kafafi, 2012; Antineskul & Sheveleva, 2015). The present paper aims to explore teachers’ perceptions of the teaching contents under the influence of an EAT which steps up to an English Proficiency Test - PET (or B1 level equivalent) for university undergraduates in Vietnam as required for graduation by Vietnam’s Ministry of Education and Training (MOET). The EAT, mirroring the PET, was designed to expect positive washback in the course English 2. The research tools were interviews with four teachers teaching the same English course. Each teacher was interviewed twice at two different time points so that their temporal developmental cognition of the EAT could be recorded. The findings revealed the heavy impact of the test on teachers’ perceptions of their teaching contents. Two dominant points were (1) all the participants thought the course primarily served the EAT orientation, particularly in the test format and the linguistic input, and (2) the teachers should strictly follow the textbook as the major instructional source. There existed a mismatch between the university’s purpose of enhancing the students’ communicative ability and the teachers’ perceptions. Differences in the teachers’ backgrounds entailed their diverse perceptions. The study provides a reference case for the interested readers in and beyond the researched context.